The Intergenerational Transmission of Cognitive Skills: An Investigation of the Causal Impact of Families on Student Outcomes - Eric A. Hanushek; Babs Jacobs; Guido Schwerdt; Rolf Van der Velden; Stan Vermeulen; Simon Wiederhold (Institute of Labor Economics (IZA), 2021)
The extensive literature on intergenerational mobility highlights the importance of family linkages but fails to provide credible evidence about the underlying family factors that drive the pervasive correlations. We employ a unique combination of Dutch survey and registry data that links math and language skills across generations. We identify a causal connection between cognitive skills of parents and their children by exploiting within-family between-subject variation in these skills. The data also permit novel IV estimation that isolates variation in parental cognitive skills due to school and peer quality. The between-subject and IV estimates of the key intergenerational persistence parameter are strikingly similar and close at about 0.1. Finally, we show the strong influence of family skill transmission on children's choices of STEM fields.
Keywords: I24; I26; J12; J24; J62; 330; intergenerational mobility; parent-child skill transmission; causality; STEM